IN-ON-IN PATTERN MENTORING: IMPROVING THE ABILITY TO DESIGN CLASSROOM ACTION RESEARCH FOR ELEMENTARY SCHOOL TEACHERS IN BUAY RUNJUNG SUB-DISTRICT - Ermis Suryana; Aliasan Aliasan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
This training and mentoring activity aims to improve the ability of SD Negeri 1 and 2 Sunur teachers to design classroom action research, especially in understanding the basic concepts and skills in preparing classroom action research proposals (PTK). The method used is participatory learning and action using the IN-ON-IN pattern with stages: In-service Training 1 (IN-1), On Job Training (ON), and In-service Training 2 (IN-2). The results achieved were an increase in participants' understanding of concepts and skills in preparing PTK proposals. This activity provides space and time for participants to apply the theory, concepts and procedures of PTK into real experience in preparing PTK proposals. The training process during IN-1 was very useful in building teachers' understanding of the concept of PTK. The mentoring process during ON made participants more focused and stable in designing PTK. Sharing experiences during IN-2 provided additional insights and reinforcement for the participants for better results. This activity is categorized as successful because the N-Gain value is in the medium and high categories.